United States, Iñupiat child holding sled dog pup in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
When this boy's pup grows up, he will be a sled dog. Sorensen 687 c1: Barrow 8. Eskimo boy at Point Barrow, Alaska Sorensen 687 c2: Eskimo boy with dog. Barrow, Alaska Portrait of native boy carrying pup. Image published in Learning to Look at Our World, page 41. Cooper, K.S., Sorensen, C.W., Todd, L.P., & Silver Burdett Company. (1969). Learning to look at our world. Morristown, N.J: Silver Burdett. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3